Analisis dan Interpretasi Data Bagi Suatu Perusahaan - Meilan Sri Desfitra; Zahwa Aulia; Rezeki Putri Utami; Nur Fitriana (CV. ITTC INDONESIA, 2024)
This study aims to conduct in-depth analysis of data collected from a company to identify patterns, trends, and insights that can support strategic decision-making. The methods used include statistical data processing and advanced data analysis techniques to uncover relationships among variables and predict future outcomes. The results of this study demonstrate the importance of applying data analysis in enhancing operational efficiency and business strategy for the company. The implications of these findings can provide guidance for companies in optimizing resources and improving overall performance.